NUTRITIONAL VALUE OF BUCKWHEAT FLOUR-BASED SEMI-FINISHED BISCUIT - MAZURENKO, IGOR; BOKOVETS, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article substantiates the theoretical aspect of green buckwheat flour and psyllium as innovative components for use in the technology of the "Bushe" flour semi-finished product. Buckwheat flour has been chemically proven to be a valuable source of vegetable protein, as it contains high levels of protein and amino acids such as lysine and tryptophan, which may be limited in other cereal crops. It also became known that this type of flour has a low glycemic index and is a hypoallergenic product. In addition, green buckwheat flour is a source of minerals such as iron, magnesium, phosphorus and manganese, which contribute to bone, heart and immune system health. Thanks to its pleasant taste and texture, it becomes an excellent ingredient for baking, adding useful nutrients to bakery products.In turn, psyllium improves the texture of products, increasing their volume. It is a known source of soluble fiber. The content of soluble fibers in psyllium exceeds other sources of fibers, which are contained in such products as oats, flax or sunflower. It contains antioxidants such as flavonoids and phenolic compounds that can help reduce inflammation and fight stress in cells. It can be added in powder or husk form to foods to increase fiber content and improve texture.The theoretical substantiation of the innovative raw material: green buckwheat and psyllium flour showed that this raw material can be used for the development of a new recipe and improvement of the technology of a whipped biscuit semi-finished product of the "Bouche" type.According to the results of the research, it was found that the addition of a mixture of green buckwheat flour and psyllium made it possible to significantly improve the nutritional and biological value of ZBN, increasing the content of macronutrients, namely proteins and micronutrients, vitamins and minerals, and makes this product useful and nutritious, meeting modern requirements for healthy food.
Keywords: whipped biscuit semi-finished product; green buckwheat flour; psyllium; "Bouche" biscuit; nutritional value